2018
DOI: 10.1038/s41598-018-35849-8
|View full text |Cite
|
Sign up to set email alerts
|

Shape changes of erythrocytes during blood clot contraction and the structure of polyhedrocytes

Abstract: Polyhedral erythrocytes, named polyhedrocytes, are formed in contracted blood clots and thrombi, as a result of compression by activated contractile platelets pulling on fibrin. This deformation was shown to be mechanical in nature and polyhedrocytes were characterized using light and electron microscopy. Through three-dimensional reconstruction, we quantified the geometry of biconcave, intermediate, and polyhedral erythrocytes within contracting blood clots. During compression, erythrocytes became less oblate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 43 publications
1
58
0
Order By: Relevance
“…Figure 3C) are reminiscent of polyhedrocytes observed in contracted thrombi. 15,16 Thrombus contraction was reported to be reduced in patients with ischemic stroke, but could have profound effects on thrombus organization, thrombus volume (and thus blood flow past thrombo-embolic occlusions) and thrombus density. 17 More studies are needed to fully understand the potential effect of thrombus contraction in ischemic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3C) are reminiscent of polyhedrocytes observed in contracted thrombi. 15,16 Thrombus contraction was reported to be reduced in patients with ischemic stroke, but could have profound effects on thrombus organization, thrombus volume (and thus blood flow past thrombo-embolic occlusions) and thrombus density. 17 More studies are needed to fully understand the potential effect of thrombus contraction in ischemic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Polyhedrocytes have been observed in human coronary thrombi21; it is hypothesized that this shape allows for more efficient packing of RBCs,11 thus creating an impermeable seal at the site of vessel injury to prevent bleeding 10. This decreased permeability may impact the effectiveness of medical thrombolytic therapy in AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, clot contraction acts to create an impermeable seal at the site of vessel injury. It has been found that the extent of clot contraction is sensitive to hematocrit—the volume percentage of red blood cells (RBCs) in the blood (%H),11 fibrinogen concentration and platelet function.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, other studies have also considered the role of cellularity in thrombus mechanics (Gersh et al, 2009;Kim et al, 2017). These studies have found that closely-packed elements significantly alter the mechanical behavior of thrombus (Tutwiler et al, 2018;van Oosten et al, 2019) requiring a holistic approach toward studying thrombus. Additionally, the constitution and thus mechanics of in-vivo thrombi are not time-invariant (Rausch and Humphrey, 2017).…”
Section: Introductionmentioning
confidence: 99%